No more “Us’’ Versus “Others”: Critique of Cultural Trauma in the Movie Partition by Vic Sarin - Lamichhane, Yog Raj (Literary Studies, 2021)
On 15 August 1947, the glory of Indian Independence has introduced with a political hubris, dividing British India into two separate independent nations: secular India and Islamic Pakistan. The partition brings trauma in the life of millions; nevertheless, this trauma itself becomes the victim of nationhood and community both in official history and literary writing. In this background, the study examines how a Hollywood movie Partition directed by Vic Sarin in 2007, exceptionally surpasses that tendency of dividing the community into ‘‘as’’ and ‘‘others’’ imparting Indian partition trauma politically. While analyzing the behavior and action of major characters along with the overall imparted theme of the movie, it rethinks the customary archives of community and nationhood depicting partition memory objectively. The protagonist never pronounces a single word of communal intolerance even when he has been mocked and tortured in the name of religion. Conversely, some characters in the movie always attempt to massacre the truth of trauma spreading communal bile; however, the overall essence and message of the movie keep that alive. Rethinking cultural trauma and using the approach of memory, the study concludes that this in-between movie appears as “West Running Brook” that exceeds the common communalization and perpetual politicization in the history of depicting Indian partition. Eventually, the study establishes that sharing pain seems to work as a healer among victims to overcome their trauma on one side and uniquely it adjoins the British as a party in Indian partition trauma in the next, which has been blurred considering insignificant in the one-to-one conflict between two giants.